Effect of Integrated Application of Inorganic and Organic Sources on Soil Properties, Yield and Nutrient Uptake by Rice (Oryza sativa L.) in Intermediate Zone of Jammu and Kashmir - Tabasum Nazir Qadri, Q.J.A. Peer, M.A. Dar and I.A. Bisati, M.H. Chesti, Anshuman Kohli, Aziz Mujtaba, J.A. Sofi (Journal of the Indian Society of Soil Science, 2015)
Field experiment was conducted for three consecutive kharif seasons (2009 to 2011) at the Crop Research Farm, RARS, SKUAST-Jammu, Rajouri to study the effect of integrated application of inorganic and organic sources on soil properties, yield and nutrient uptake by rice in intermediate zone of Jammu and Kashmir. Three years of conjoint use of 10 t FYM ha-1 with 100% NPK significantly improved the organic carbon and available N, P and K contents over the chemical fertilizers alone. Significantly higher grain yield of 5.36 t ha-1 and total NPK uptake by rice (96.3, 20.4 and 109.5 kg ha-1, respectively) with the application of 100% NPK+10 t FYM ha-1 as compared to the grain yield of 4.96 t ha-1 and total NPK uptake (86.5,18.1 and 96.8 kg ha-1, respectively) with the 100% NPK alone. The yield and nutrient uptake by rice were significantly lower with the sub-optimal doses of NPK. Addition of Zn did not improve rice yield significantly. Thus, integrated application of inorganic and organic sources (100% NPK + 10 t FYM ha-1) maximized yields of rice crop and improved the soil fertility in the intermediate zone of Jammu and Kashmir.